Incidencia de anemia post parto y sus factores de riesgo en gestantes adolescentes ingresadas al Hospital General Alfredo Noboa Montenegro periodo enero - junio 2024. - Carrasco Lara, Mishel Nataly (2024)
Anemia is a prevalent problem over the years, affecting pregnant women more recurrently, and being much more notable in the postpartum period where it has an impact on the physical and emotional well-being of the postpartum woman. The objective of this project is to determine the incidence of postpartum anemia and its risk factors in pregnant adolescents admitted to the Alfredo Noboa Montenegro General Hospital during the period January-June 2024. This research will adopt a quantitative approach to analyze in depth the incidence of postpartum anemia. and its risk factors in pregnant adolescents admitted to the Alfredo Noboa Montenegro General Hospital. In this research, the population will be made up of 367 pregnant adolescents. In this case, the sample will consist of 188 pregnant women. The collected data were entered into a Microsoft Excel 2021 spreadsheet, where each row represents a patient and each column a specific variable, such as age, preconception nutritional status, etc. The study revealed that postpartum anemia is prevalent among pregnant adolescents, with low socioeconomic status, incomplete or no iron supplementation, and postpartum hemorrhages being the main associated risk factors. Although postpartum hemorrhage did not show a statistically significant relationship, its high prevalence suggests that it is an important factor. These findings underscore the need for comprehensive and multidimensional interventions in prenatal and postnatal care to reduce the incidence of postpartum anemia in adolescents.